2015
DOI: 10.3906/sag-1405-96
|View full text |Cite
|
Sign up to set email alerts
|

Potential genetic biomarkers in the early diagnosisof Alzheimer disease: APOE and BIN1

Abstract: Background/aim: Alzheimer disease (AD) is triggered by interactions of multiple genetic and environmental factors. The APOE gene E4 allele is the best-known risk factor for AD, yet it represents a small ratio of genetic factors. According to genome-wide association studies, the BIN1 gene is the second important risk factor for AD, following the APOE gene. We aimed to identify a novel biomarker indicating susceptibility to AD by investigating APOE alleles and BIN1 gene polymorphisms in a Turkish population.Mate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…The first, rs6733839, has been widely reported as a risk variant in various populations, however, in AAs there was no strong evidence of association 37 . The second, rs744373, was identified as a risk variant in Japanese with no evidence for association in AA or Turkish populations 38 . Following targeted sequencing and follow-up genotyping, Vardarajan et al, 2015 found BIN1:p.Lys358Arg (rs138047593) in 8 Caucasian and 6 Hispanic LOAD patients; segregation was shown in 2 out of 6 Caribbean Hispanic families 39 .…”
Section: Translatability Of Known Ad Gwas Hits To Datementioning
confidence: 99%
“…The first, rs6733839, has been widely reported as a risk variant in various populations, however, in AAs there was no strong evidence of association 37 . The second, rs744373, was identified as a risk variant in Japanese with no evidence for association in AA or Turkish populations 38 . Following targeted sequencing and follow-up genotyping, Vardarajan et al, 2015 found BIN1:p.Lys358Arg (rs138047593) in 8 Caucasian and 6 Hispanic LOAD patients; segregation was shown in 2 out of 6 Caribbean Hispanic families 39 .…”
Section: Translatability Of Known Ad Gwas Hits To Datementioning
confidence: 99%